2008
DOI: 10.1002/jcop.20196
|View full text |Cite
|
Sign up to set email alerts
|

Diversity within: subgroup differences of youth problem behaviors among asian pacific islander American adolescents

Abstract: This study compares problem behaviors across a range of adolescent Asian Pacific Islander (API) subgroups using the Add Health data, and controlling for parental education or immigrant status. The study finds that Filipino, "other" API, and multiethnic API American youth are at higher risk for poorer outcomes than Chinese, Korean, and Vietnamese American counterparts. Many of these differences remained after adjusting for parental education. Controlling for immigrant status explained only some of the subgroup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 20 publications
2
65
1
Order By: Relevance
“…Compared to Asians, Pacific Islander youth endorse significantly greater risk factors suicide. This finding is consistent with previous literature illustrating considerable differences in health-risk behaviors between the two API ethnic groups (Choi, 2008;Sasaki & Kameoka, 2009;Wong, Klingle, & Price, 2004).…”
Section: Ethnicity and Adolescent Suicidalitysupporting
confidence: 94%
See 2 more Smart Citations
“…Compared to Asians, Pacific Islander youth endorse significantly greater risk factors suicide. This finding is consistent with previous literature illustrating considerable differences in health-risk behaviors between the two API ethnic groups (Choi, 2008;Sasaki & Kameoka, 2009;Wong, Klingle, & Price, 2004).…”
Section: Ethnicity and Adolescent Suicidalitysupporting
confidence: 94%
“…And fifth, the YRBS fails to disaggregate within each of the Asian, Pacific Islander, and multiracial populations. Studies of Asian subgroups have already demonstrated that ethnic subgroups within these categorical umbrellas may show diverging trends of youth risk behavior prevalence (Choi, 2008;Mayeda, Hishinuma, Nishimura et al, 2006). Our findings also show that within the multiracial population, those identifying as part-Hispanic reported a lower prevalence of suicide ideation and planning compared to their non-Hispanic multiracial peers.…”
Section: Ethnicity and Adolescent Suicidalitymentioning
confidence: 96%
See 1 more Smart Citation
“…However, those differences may result from differences in generational status rather than country of origin. Some studies showed higher proportions of high risk sexual behaviours among Japanese American adolescents than Chinese American adolescents (Choi, 2008;Nagasawa, Qian, & Wong, 2001). However, when generational status was controlled for, there were no longer any differences between Chinese Americans, who were more likely to be immigrants or second generation, and Japanese Americans, most of whom were third or higher generation.…”
Section: Study Limitationsmentioning
confidence: 80%
“…The Korean community has a recent trend of immigration history in the United States (Choi, 2008;Yeh, 2003).…”
Section: Introductionmentioning
confidence: 99%